Qualitative and Quantitative Methods in Sustainable Development 2021
DOI: 10.18559/978-83-8211-072-2/03
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis in sustainable development research

Abstract: Too much data describing a given phenomenon requires synthesizing them. For this purpose, researchers can use various methods of analysis. Factor analysis is one of them. In this section, first the basic theoretical aspects of factor analysis, as well as the stages of its use are described while presenting the essential minimum necessary to understand the essence of the method. The second part presents an example of the use of this method in research on sustainable consumption. The last part of this chapter pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Researchers can use only quantitative, only qualitative, or mixed methods, depending on the nature of the study. Olejnik (2021) stated that qualitative research is the act of gathering and analyzing non-numeric data, such as interview transcripts, videos, audios, or photos. This data helps to comprehend ideas, discover the core of certain phenomena, or explore viewpoints or experiences related to a particular issue.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers can use only quantitative, only qualitative, or mixed methods, depending on the nature of the study. Olejnik (2021) stated that qualitative research is the act of gathering and analyzing non-numeric data, such as interview transcripts, videos, audios, or photos. This data helps to comprehend ideas, discover the core of certain phenomena, or explore viewpoints or experiences related to a particular issue.…”
Section: Methodsmentioning
confidence: 99%
“…This test assesses how well our data are prepared for factor analysis. For this test, 0.8 and above is the optimum scenario to accept the factors for further analysis [64]. Table 2 below shows the KMO test statistics, which in our case is 0.962.…”
Section: Exploratory Factor Analysismentioning
confidence: 97%
“…Cronbach's Alpha test, an SPSS built-in tool, was used to assess the dataset's reliability. The following steps (see Figure 1) in the factor analysis sustainability research were adapted as suggested by Knežević, and Stefa ńska [64].…”
Section: Exploratory Factor Analysis (Efa)mentioning
confidence: 99%